"Impact of Awareness Campaign in Implementation of Sanitation Programmes" - Shruthi J; G. Sudarsana Reddy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Defecation practices in India are guided by the idea of profanity and sacredness. Defecating in the open is a common practice that pervades across the states of India. The government has been trying to change this behaviour of the people in the country by providing several infrastructural facilities. It took several decades to achieve the target of providing the infrastructure, but changing the behaviour still continues to be a daunting task to the government. This paper explores the trajectory of India becoming a country free of Open Defecation and the need for an Information and Education Campaign to achieve the target. The paper lists several programmes initiated by the Government of India for the past few decades and investigates how the investment in Information and Education Campaign influenced upon the effectiveness of the programme. Several data collected from various sources are compared to arrive at a conclusion which throws light on the methods to sharpen the effectiveness of these policies.